The role of archives in creating national identity and harmony in post-communist society. Issue 1 (January 2018) - Czajka, Elzbieta
Abstract : This paper describes the transformation of the archival paradigm in Poland following the end of the communist era in 1989. Previously, archives were disconnected from ordinary people and functioned primarily to bolster the official narratives of the communist rulers, serving only a narrow cohort of scientific and official users. Nowadays, Polish archives are open and democratic institutions that actively encourage grassroots community engagement and encourage research into local history and genealogy. This transformed archival role supports the development of local, regional and national identities and social harmony.